Comparison of oropharyngeal leak pressure and insertion characteristics of Ambu AuraGain and i-gel in patients undergoing laparoscopic inguinal hernia repair: A randomized control trial - Anupma; Swati Chhabra; Sadik Mohammed; Manoj Kamal; Rakesh Kumar; Pradeep Bhatia (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Airway protection and adequate ventilation are the main aim for the patients undergoing laparoscopic surgeries under general anesthesia. The study intended to compare the oropharyngeal leak pressure (OLP) and insertion parameters and postoperative complications between Ambu AuraGain and i-gel in laparoscopic hernia repair surgeries. The primary objective was to compare the OLP at insertion and after pneumoperitoneum and positioning. The secondary objectives were to compare the time required for insertion, number of attempts, ease of insertion, and ability to insert gastric tube, grade of fiber-optic glottic view and postoperative complications. Material and Methods: A randomized controlled trial of 50 patients belonging to American Society of Anesthesiologists (ASA) physical status grade I and II, aged between 18–60 years, was randomly divided into group AAG and Group IG. Results: No significant difference was found between the two groups in terms of OLP at insertion and 5 min after pneumoperitoneum. However, OLP at 30 min of pneumoperitoneum was statistically higher with Ambu AuraGain than i-gel (27.72 ± 2.67 cm H2O versus 25.50 ± 2.38 cm H2O; P value = 0.002). The fiber-optic glottic view was better with Ambu AuraGain than i-gel at 5 min and 30 min after pneumoperitoneum (P value = 0.038 and 0.043, respectively). Ambu AuraGain took longer insertion time compared to i-gel which was statistically significant. Conclusions: The OLP and fiber-optic glottic view of Ambu AuraGain are better than i-gel with longer insertion time, and the rest of the variables were comparable. We conclude that Ambu AuraGain is superior to i-gel in adult patients undergoing laparoscopic inguinal hernia repair under general anesthesia.